Penyuluhan dan Praktik Budidaya Tayurdapot untuk Kelompok Tani “Abdi Dalem Klebengan”, Kelurahan Kadipiro, Banjarsari, Surakarta - Sudadi Sudadi; Slamet Minardi; Ongko Cahyono; Vita Ratri Cahyani; Siti Maro'ah (PRIMA: Journal of Community Empowering and Services, 2024)
Counseling and Practices of Tayurdapot Cultivation for Farmers Group “Abdi Dalem Klebengan”, Kadipiro Village, Banjarsari, Surakarta. Citizens association (RW) 17 as a partner in this community service activity is one of the RWs in Kelurahan Kadipiro, Banjarsari District, Surakarta City which has a farmer group, namely the Farmer Group (Poktan) "Abdi Dalem Klebengan" which until now has been very active in empowering the community in agriculture. Even though it is located in the city area, Poktan "Abdi Dalem Klebengan" realizes that agricultural activities are one of the sectors that can help maintain the community's economy. Therefore, Poktan "Abdi Dalem Klebengan" is very active in trying to make the people in their area, namely RT 01 RW 17, work on agriculture around their settlements, including in the yards of their respective houses by working on potted plants to help the family's economy. One type of plant that is easy to cultivate in a pot is a vegetable plant (Plant vegetables in a Pot-Tayurdapot). This service activity aims to awaken and maintain the spirit of farming around the house for members of the Poktan "Abdi Dalem Klebengan" in particular and the community of RT 01 RW 17 Ngipang, Kadipiro, Banjarsari, Surakarta in general. Activities are carried out by the method of socialization activities and demonstrations of Tayurdapot cultivation practices in synergy with the Poktan "Abdi Dalem Klebengan". Through this effort, it is hoped that the families of the group members and the community of RT 01 RW 17 will be helped by their need for vegetables that can reduce daily shopping costs. Poktan "Abdi Dalem Klebengan" also produces organic fertilizer from its livestock business so that it can synergize with this service activity through its help organic fertilizer as a planting medium for tayurdapot for residents of RT 01 RW 17. This service activity is mono-year, but is expected to continue in the following year through other productive activities such as tabulampot, livestock business, fish rearing and guidance on the production of organic fertilizers and liquid biofertilizers.